Numerical Interchain Mean-Field Theory for the Specific Heat of the Bimetallic Ferromagnetically Coupled Chain Compound MnNi(NO2)4(en)2 (en = Ethylenediamine) - Andreas Honecker; Wolfram Brenig; Maheshwor Tiwari; Ralf Feyerherm; Matthias Bleckmann; Stefan Süllow (Molecules, 2022)
We present a detailed study of the field-dependent specific heat of the bimetallic ferromagnetically coupled chain compound MnNi(NO<semantics>2</semantics>)<semantics>4</semantics>(en)<semantics>2</semantics>, en = ethylenediamine. For this material, which in zero field orders antiferromagnetically below <semantics>TN=2.45</semantics> K, small fields suppress magnetic order. Instead, in such fields, a double-peak-like structure in the temperature dependence of the specific heat is observed. We attribute this behavior to the existence of an acoustic and an optical mode in the spin-wave dispersion as a result of the existence of two different spins per unit cell. We compare our experimental data to numerical results for the specific heat obtained by exact diagonalization and Quantum Monte Carlo simulations for the alternating spin-chain model, using parameters that have been derived from the high-temperature behavior of the magnetic susceptibility. The interchain coupling is included in the numerical treatment at the mean-field level. We observe remarkable agreement between experiment and theory, including the ordering transition, using previously determined parameters. Furthermore, the observed strong effect of an applied magnetic field on the ordered state of MnNi(NO<semantics>2</semantics>)<semantics>4</semantics>(en)<semantics>2</semantics> promises interesting magnetocaloric properties.